1990
DOI: 10.1128/jcm.28.9.2051-2058.1990
|View full text |Cite
|
Sign up to set email alerts
|

Insertion element IS986 from Mycobacterium tuberculosis: a useful tool for diagnosis and epidemiology of tuberculosis

Abstract: M. tuberculosis Clinical isolates This laboratory 3, 5, 10 M. tuberculosis Clinical isolates (Ghana) T. van der Werft 92, 93, 95-101 M. tuberculosis Clinical isolates (outbreak in The Netherlands) This laboratory 107-128, 130-133 M. tuberculosis Clinical isolates (Tilburg, The Netherlands) P. L. van Puttenb 38 M. africanum Clinical isolate This laboratory 40, 41 M. bovis Clinical isolates This laboratory 43, 45, 105, 106 M. bovis BCG Clinical isolates This laboratory 102 M. bovis BCG Vaccine strain Organon Tek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
163
1
11

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(183 citation statements)
references
References 20 publications
8
163
1
11
Order By: Relevance
“…The clinical isolates of M. tuberculosis studied with these probes displayed a high degree of polymorphism and the long term stability of RFLP has been demonstrated. Indeed, IS6110 RFLP analysis of strains isolated from patients at two-and threeyear intervals showed identical patterns [8] whereas studies performed with the IS986 probe that differs from IS6110 by 3 nucleotides have shown the genetic stability of IS986 after guinea pig passage of the strains [9] or during multiple in vitro passages [7]. Our study confirms the high degree of polymorphism using the IS6110 be-295 tween unrelated clinical strains and the identity of the RFLP banding patterns among related clinical strains.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The clinical isolates of M. tuberculosis studied with these probes displayed a high degree of polymorphism and the long term stability of RFLP has been demonstrated. Indeed, IS6110 RFLP analysis of strains isolated from patients at two-and threeyear intervals showed identical patterns [8] whereas studies performed with the IS986 probe that differs from IS6110 by 3 nucleotides have shown the genetic stability of IS986 after guinea pig passage of the strains [9] or during multiple in vitro passages [7]. Our study confirms the high degree of polymorphism using the IS6110 be-295 tween unrelated clinical strains and the identity of the RFLP banding patterns among related clinical strains.…”
Section: Discussionsupporting
confidence: 77%
“…It has been shown that transposition of these IS elements was a rare event in the M. tuberculosis complex strains grown either in vitro or in vivo for long periods of time. Indeed, strains from three patients who developed tuberculosis showed identical patterns in RFLP analysis at two-or three-year intervals in a study using IS6110 as the epidemiological marker [8] and no change of fingerprintings using the IS986 element was observed during in vitro [7] or in vivo [9] passages of M. tuberculosis in experimental animals. In more recent studies, DNA fingerprinting with IS6110 as the probe was used to determine whether a subject who died of tuberculous meningitis had been infected by a neighbour [10], and also to investigate a tuberculosis outbreak in a residencial facility for HIV-infected patients [11].…”
Section: Introductionmentioning
confidence: 97%
“…The standard genotyping method, IS6110 RFLP typing [4] is based on a small DNA sequence that is capable of creating copies of itself within the genome [20,21]. IS6110 RFLP typing cleaves the M. tuberculosis genome and identifies the number of copies of IS6110 within the genome and the size of the genomic DNA fragments they are on, creating a pattern that looks similar to a bar code.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…Other techniques suffer from problems of reproducibility and low numbers of different types (18,24). Since the discovery of polymorphic DNA in Mycobacterium tuberculosis, strain differentiation has become an important tool in the epidemiology of tuberculosis (39 digoxigenin labeling of a 245-bp fragment obtained through amplification by polymerase chain reaction (PCR) (17). Briefly, the oligonucleotides INS-1 (5'-CGTGAGGGCATCGAGGTGGC) and INS-2 (5'-GCG-TAGGCGTCGGTGACAAA) were used to amplify a 245-bp fragment from purified chromosomal M. bovis BCG DNA by PCR using a DNA thermal cycler (Perkin Elmer Cetus).…”
mentioning
confidence: 99%